MODEL INTEGRASI ILMU DI INDONESIA - Halimatussa’diyah Halimatussa’diyah (CV. ADIBA ASIHA AMIRA, 2023)
This article focuses on the integration of Islamic teachings facilitated by the existence of a dualism or dichotomy between the teachings of Islam and the teachings of other religions. The implications are broad, not only affecting Islamic education policies, but also Islamic education policies in general, as well as Islamic education policies in particular, including Islamic education policies in general, and Islamic education policies in particular. The Islamic worldview can be put into various models. The method used is library research, the results of this research are IFIAS, ASASI, Islamic World View, and Islamic Knowledge Structure. Integration of Classical Philosophy-Based Science, Fiqh-Based Sufism, Ijmali Group Model, and Aligarh Group.